2016
DOI: 10.1589/jpts.28.547
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-II blockage, muscle strength, and exercise capacity in physically independent older adults

Abstract: [Purpose] This study aimed to assess the exercise capacity and muscle strength in elderly people using drugs for angiotensin-II blockage. [Subjects and Methods] Four hundred and seven older adults were recruited for this study. Data about comorbidities and medication use were recorded and the individuals were divided into three groups: control group- elderly people with normal exercise capacity (n=235); angiotensin-converting enzyme inhibitor group − individuals using angiotensin-converting enzyme inhibitors (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 32 publications
1
17
2
Order By: Relevance
“…Some studies suggest that aldosterone blockade may reduce decline in physical function by reducing muscle strength, but the majority of studies on the RAS have examined angiotensin‐converting enzyme inhibitor (ACE‐I) use . Two investigations provide some evidence of a reduction in disability, exercise capacity, and muscle strength directly, and a review of studies showed a beneficial effect of ACE‐Is and angiotensin receptor blockers on exercise capacity, although the exact mechanisms are unclear . Our results indicated a protective association between RAS blockers and risk of decline but only in the low polypharmacy group, although sensitivity analysis showed that, if 15% or more of the decedents had declined, then the protective association lost significance, suggesting that this result is not robust to losses due to death.…”
Section: Discussionmentioning
confidence: 59%
“…Some studies suggest that aldosterone blockade may reduce decline in physical function by reducing muscle strength, but the majority of studies on the RAS have examined angiotensin‐converting enzyme inhibitor (ACE‐I) use . Two investigations provide some evidence of a reduction in disability, exercise capacity, and muscle strength directly, and a review of studies showed a beneficial effect of ACE‐Is and angiotensin receptor blockers on exercise capacity, although the exact mechanisms are unclear . Our results indicated a protective association between RAS blockers and risk of decline but only in the low polypharmacy group, although sensitivity analysis showed that, if 15% or more of the decedents had declined, then the protective association lost significance, suggesting that this result is not robust to losses due to death.…”
Section: Discussionmentioning
confidence: 59%
“…Medications commonly used in older individuals, such as ACEi, have been reported to attenuate age-related decline in physical performance (8,23,24,52) and increase life span (53)(54)(55). However, treatments with ACEi are not always effective (13) and determinants of inter-individual variation in response to ACEi are largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Two drug classes that inhibit RAS by directly targeting Ang II, the ACE inhibitors (ACEi) and the angiotensin receptor blockers (ARBs), are widely used in clinical practice to manage cardio-vascular disorders and chronic kidney disease [ 2 ]. More recent evidence suggests that administration of ACEi or ARBs can also improve physical function in older individuals with impairment of daily activities [ 5 ] and in physically independent elderly people [ 6 ]. Moreover, ACEi or ARB-induced blockade of RAS has been shown to reduce the incidence of type-2 diabetes in patients with heart failure or at risk for coronary artery disease [ 7 ] and ameliorate skeletal muscle insulin sensitivity in mammalian models [ 8 ].…”
Section: Introductionmentioning
confidence: 99%